DESIGN OF JLANTAH MINI HYDRO POWER PLANT (PLTM) IN JLANTAH RESERVOIR, KARANGANYAR REGENCY, CENTRAL JAVA. - Catlyea Harahap, Adinda
The increasing number of electricity users in Jatiyoso District, Central Java, has occurred in recent years. In 2020, the number of electricity users in Jatiyoso District was recorded at 12,773 households, an increase of 79 households compared to 2019. This increase in electricity demand must be balanced with an increase in the source of electricity for the community. Therefore, by building the Jlantah Mini Hydro Power Plant (PLTM), it is expected to become one of the sources of electricity for the local community. The normal water level of the reservoir is planned at an elevation of +691.00 meters above sea level (masl) and the intake building elevation is at +661.00 masl. The total dead storage of the reservoir is 1.66 million ????3 and the total effective storage is 9.16 million ????3. The elevation of the power plant building is planned by analyzing the 100-year flood in the river around the power plant building plan. The power plant building is planned at an elevation of +624.00 masl. There are two turbines used in the power plant, with Turbine 1 having the HLA550-WJ-55 series and Turbine 2 having the HLA678-WJ-50 series. The average power generated in a normal year (2013) is 516.44 kW with a total energy of 4.47 GWh. The construction cost of the Jlantah PLTM is estimated to reach IDR 18,795,716,076.00 with normal annual revenue (2013) of IDR 4,060,935,522. With this revenue, the NPV value is IDR 4,461,454,224, IRR 12.96%, BCR 1.24, and PBP 12.78 years, making this project economically feasible.